A natural tetranortriterpenoid with immunomodulating properties as a potential anti-HSV agent - Bueno, Carlos Alberto (2009)
Meliacine (MA), an antiviral principle present in partially purified leaf extracts of Melia azedarach L., prevents the development of herpetic stromal keratitis (HSK) in mice by diminishing the viral load in the eye and the severity of lesions caused by a virus-induced immunopathological reaction. The tetranortriterpenoid 1-cinnamoyl-3,11-dihydroxymeliacarpin (CDM), obtained from MA purification, displays anti-herpetic activity and impedes nuclear factor κB (NF-κB) activation in HSV-1 infected conjunctival cells. To extend our understanding about CDM biological properties, we investigated its anti-HSV-1 activity as well as the effect on NF-κB activation and cytokine secretion induced by viral (HSV-1) and no-viral (LPS) stimuli, in corneal cells and macrophages. CDM exerted a potent anti-HSV-1 effect on corneal cells and inhibited NF-κB translocation to the nucleus, leading to a decrease in IL-6 production. Besides, CDM seemed to modulate IL-6 and TNF-α responses in macrophages, whether they were infected with HSV-1 or stimulated with LPS. However, CDM did not affect NF-κB activation in these cells, suggesting that an alternative NF-κB cell signaling pathway would be involved in the modulation of cytokine production. We conclude that, in addition to its antiviral effect, CDM would be acting as an immunomodulating compound which would be responsible for the improvement of murine HSK already reported. © 2008 Elsevier B.V. All rights reserved.